Eritrea’s Youth Migration Challenge: The Role of Aspirations and Opportunity - Mac-Ikemenjima , Dabesaki; Gebregiorgis, Helen (African Human Mobility Review, 2021)
Over the last decade, Eritrea has received significant analyses from the mainstream media and some scholars, due to the mass international migration of its citizens, estimated at 5,000 individuals monthly, especially youth. The aim of this paper is to explore factors that explain the mass migration of Eritrean youth, with a focus on the potential roles of aspirations and opportunities. Much of the literature suggests that young Eritreans are emigrating due to their countryâ€™s national service program. We analyse the literature on the factors driving Eritrean youth migration vis-Ã -vis push factors for migration from subSaharan Africa. Based on our analysis of various bodies of work related to Eritrean migration and aspirations, we conclude that three main factors explain youth migration from Eritrea: 1) tensions between individual and national aspirations; 2) limited opportunities for transition from education to employment; and 3) limited rights and freedoms.